Antihypertensive therapy effectiveness in patients with arterial hypertension and varying risk of cardiovascular events - I. E. Chazova; L. G. Ratova (Кардиоваскулярная терапия и профилактика)
Aim. To study antihypertensive effectiveness and safety of amlodipine as monotherapy and in combination with carvedilol in patients with arterial hypertension (AH), taking into account total risk of cardiovascular events (CVT). Material and methods. The study included 210 AH patients: 36% males, 64% females; mean age - 57+10 years, AH duration - 10+9 years. After 3-10 "wash-out" days, clinical blood pressure (BPclin.) level was 158+11/96+7 mmHg, Stage I AH was observed in 49% of the participants, Stage II - in 51%. Moderate, high, or very high CVE risk was registered in 19%, 53%, and 28%, respectively.Results. After 16 weeks of amlodipine treatment, as monotherapy and combined with carvedilol, BP clin. Was reduced by -27,7±11,7/-15,3±7,0 mm Hg (p<0,0001), heart rate (HR) – by 3,0±8,2 bpm (p=0,001). Among those receiving amlodipine monotherapy, target BP level was achieved in 75% of the patients, among those administered combined therapy – in 97%. In the control group, 16-week therapy was associated with BP clin. Reduction by -19,5±12,0/-10,2±7,2 mmHg (p<0,0001), HR – by 2,2±8,6 bpm (p<0,001); target BP level was achieved in 51% only. For high or very high CVE risk, target BP level was achieved significantly more often in the main group than in the group of non-standardized antihypertensive therapy – 97% vs 46% (p<0,001). CVE risk reduction was observed mostly in patients receiving amlodipine as monotherapy or combined with carvedilol.Conclusion. Amlodipine treatment, as monotherapy or combined with carvedilol, not only reduced BP to target levels in most patients, but also improved long-term prognosis, due to CVE risk reduction. In patients with high or very high CVE risk, combined therapy is typically needed to achieve target BP levels.